Allusion in William Blake’s Selected Poems - Prafitri, Wilma; Nasir, Muhammad Alim Akbar; Triyoga, Anwar Ibrahim (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This research conducts a comprehensive analysis about the Allusion on William Blake’s Selected Poems. The researchers choose three famous poems by William Blake such as ‘The Tyger’,’The Lamb’ and ‘A Poison Tree’. The researchers explored several types of allusion such as religious allusion, literary allusion, historical allusion, and mythical allusion. Furthermore, the researchers also explored autobiographical allusions in order to find the implication of allusion in the poems and Blake’s personal experience and philosophy. Using Bezerman’s approach, the researchers concluded several points. First, the researchers found twelve allusions in Blake’s selected poems. Specifically, there are three religious allusions, three mythical allusions, and two literary allusions in the Tyger. Furthermore, the researchers identified two religious allusions in The Lamb. In ‘A Poison Tree’ there are two religious allusions and two mythical allusions. Allusion is a powerful literary device that connects a text to other works, events, or ideas, enriching the reader's understanding through these connections. In the case of William Blake's poetry, allusion plays a critical role in creating layers of meaning, allowing readers to explore deeper interpretations and examine broader themes.